2018
DOI: 10.1002/cam4.1933
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of the quality of head and neck cancer imaging guidelines using the AGREE II tool: A EuroAIM initiative

Abstract: BackgroundDiagnostic imaging guidelines are increasingly embraced in oncologic imaging in order to improve examinations appropriateness and technical quality. The usefulness of guidelines employment in clinical practice is dramatically related to the quality of the guidelines themselves. However, an extreme variability in guidelines’ quality may occur. Following a European Network for the Assessment of Imaging in Medicine (EuroAIM) initiative, the aim of this study was to assess the quality of the available gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
(57 reference statements)
2
19
0
Order By: Relevance
“…Evaluations of CPGs for paediatric hearing loss and newborn hearing screening found that the majority of guidelines scored <60% in multiple domains. Similar findings have been found in reviews of guidelines for imaging of adult head and neck cancers and management of paediatric type 2 diabetes mellitus 8,34 . Given that the only guideline receiving a ‘High’ score overall explicitly mentioned the use of published guideline development manuals, we strongly recommend that future CPG developers and reviewers make use of AGREE II guidelines when formulating their recommendations, especially given they are among the main stakeholders for whom AGREE II was developed 35 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Evaluations of CPGs for paediatric hearing loss and newborn hearing screening found that the majority of guidelines scored <60% in multiple domains. Similar findings have been found in reviews of guidelines for imaging of adult head and neck cancers and management of paediatric type 2 diabetes mellitus 8,34 . Given that the only guideline receiving a ‘High’ score overall explicitly mentioned the use of published guideline development manuals, we strongly recommend that future CPG developers and reviewers make use of AGREE II guidelines when formulating their recommendations, especially given they are among the main stakeholders for whom AGREE II was developed 35 .…”
Section: Discussionsupporting
confidence: 72%
“…Possible standardised scores range from 0% to 100%. In accordance with previous literature, 8,10 a threshold of 60% was to be considered satisfactory in each domain. The designation of ‘high’ was assigned to CPGs with ≥5 domains scoring ≥60%, ‘average’ for CPGs with 3–4 domains of ≥60%, and ‘low’ if ≤2 domains were ≥60%.…”
Section: Methodssupporting
confidence: 55%
“…Continuous variables are presented as mean ± standard deviation. Following previous experiences both with RQS and other scoring systems [22,23], inter-reader reproducibility was evaluated by calculating the intraclass correlation coefficient (ICC) for the total RQS score obtained by each study. In accordance with recent guidelines, a two-way, random-effects, single-rater, absolute agreement ICC model was used [24].…”
Section: Discussionmentioning
confidence: 99%
“…Each appraiser was asked to assign a score to each item and to the Overall Assessment section as well as to indicate whether he/she would recommend the use of the guideline in clinical practice. Whereas they had previous exposure to the AGREE II tool (15), the appraisers also carried out the freely available online training tool consisting of an overview tutorial and a practice exercise (17).…”
Section: Methodsmentioning
confidence: 99%